INDUCTION OF OVULATION AND OVARIAN CHARACTERISTICS OF PREPUBERTAL GILTS TREATED WITH HUMAN CHORIONIC GONADOTROPIN OR KISSPEPTIN - Nogueira Natal, Fabio Luis; Ferreira de Melo, Alfredo Jose; Jimenez Filho, Diego Lobon [UNESP]; Roncato Duarte, Keila Maria; Alvarez, Rafael Herrera (Inst Zootecnia, 2016)
In view of its similar structure and function to luteinizing hormone (LH), human chorionic gonadotropin (hCG) has conventionally been used as the main hormone to induce estrus and ovulation in sows. Recently, it has been demonstrated that the neuropeptide kisspeptin is associated with pituitary LH release in different mammalian species, including swine. Thus, the aim of this study was to determine whether kisspeptin-10 combined with equine chorionic gonadotropin (eCG) could be an efficient method to induce ovulation in prepubertal gilts. Thirty 5-month-old gilts weighing 78.0 +/- 8.4 kg were randomly divided into five groups of six animals each. Groups 1, 2 and 3 received 750 IU eCG, while groups 4 and 5 received saline solution. After 72 hours, the animals received 380 nmol kisspeptin-10 (group 2), 500 IU hCG (groups 3 and 4), or saline (groups 1 and 5). The treatments were applied by a single intramuscular injection. The animals were slaughtered 7 days later and ovulation was confirmed by the presence of corpora lutea in the recovered ovaries. Data were analyzed by the Kruskal-Wallis and Fisher exact tests. The number of gilts that ovulated was similar in groups 2 and 3. This number was higher in group 5 (P< 0.01) and in groups 1 and 4 (P= 0.08). The weight or size of the ovaries was not influenced by the treatments, although the number of ovulations was higher in groups 2 and 3 (P< 0.01). These results suggest that kisspeptin-10 and hCG have similar biological activity to induce ovulation in prepubertal gilts.
Keywords: eCG; hCG; kisspeptin-10; ovulation; puberty; swine